Analisis Kebutuhan E-Modul Matematika SMP Berbasis Teori Polya Pada Materi Segiempat - Iis Irmawati; Syamsuri Syamsuri; Hepsi Nindiasari; Abdul Fatah (TIRTAMATH: Jurnal Penelitian dan Pengajaran Matematika, 2021)
Abstract: Problem solving is one of the skills in 21st century learning. Students who have low problem solving skills will experience difficulties in learning mathematics. This study aims to analyze the need for teaching materials according to the stages of the pattern in completing the rectangular material. This research is a qualitative descriptive study. Data were collected by using a questionnaire sheet via Google Form and interview messages via the WhatsApp application. From the results of the math teacher's answers, it was stated that the teaching materials used were less effective in distance learning. Likewise, the results of students' answers stated that the teaching materials used had not used e-modules. Thus, the e-module based on the polya stages is expected to be used as teaching material in distance learning for quadrilateral material.